Morphometric analysis of circulus arteriosus cerebri variations in a South African cadaveric sample - Jessica Garlick; Graham Louw; Kentse Mpolokeng (Translational Research in Anatomy, 2025)
Introduction: The circulus arteriosus cerebri (CAC), or Circle of Willis, exhibits significant anatomical variability, with fewer than 50 % of cases displaying the conventional configuration. CAC variations are associated with intracranial aneurysm (IA) formation and subsequent haemorrhagic stroke. Due to limited data on CAC variations in South Africa, this study aimed to assess the prevalence and types of arterial variations in a South African cadaveric sample and to document associated IAs. Methods: This retrospective, cross-sectional and quantitative study had a sample size of 64. The CAC was dissected, removed from the base of the brain, photographed, and analysed morphologically. Variations were classified using the Ayre et al. (2021) system and recorded individually. Results: The intact samples (n = 40) were classified according to Ayre et al. (2021) and 22.5 % of the sample displayed the conventional configuration. The predominant pattern of variation was group 5 (miscellaneous patterns), and variations were commonly observed in both the anterior and posterior circulations (55 %). Individual variations were observed (n = 64 brains; 81 variations). The leading variations were unilateral posterior communicating artery (PcoA) hypoplasia (17.3 %) and aplasia (14.8 %). The anterior communicating artery (AcoA) was the most variable artery (44.4 %), with short fusion of the anterior cerebral arteries (ACAs) being the most common variation (13.6 %) affecting the AcoA. Rare findings include type 4 and 5 PcoA terminations (double P2), not previously reported in South Africa. IA frequency was insufficient for analysis. Conclusions: These variations may increase stroke and IA risk. Knowledge of CAC variations can support neurosurgical planning and execution. Further studies in a South African setting are recommended.